Natural proteins: Sources, isolation, characterization and applications - Nehete, Jitendra Y.; Bhambar, Rajendra S.; Narkhede, Minal R.; Gawali, Sonali R. (Pharmacognosy Reviews)
Worldwide, plant protein contributes substantially as a food resource because it contains essential amino acids for meeting human physiological requirements. However, many versatile plant proteins are used as medicinal agents as they are produced by using molecular tools of biotechnology. Proteins can be obtained from plants, animals and microorganism cells. The abundant economical proteins can be obtained from plant seeds. These natural proteins are obtained by isolation procedures depending on the physicochemical properties of proteins. Isolation and purification of single protein from cells containing mixtures of unrelated proteins is achievable due to the physical and chemical attributes of proteins. The following characteristics are unique to each protein: Amino acid composition, sequence, subunit structures, size, shape, net charge, isoelectric point, solubility, heat stability and hydrophobicity. Based on these properties, various methods of isolation exist, like salting out and isoionic precipitation. Purification of proteins is quiet challenging and, therefore, several approaches like sodium dodecyl sulfate gel electrophoresis and chromatography are available. Characterization of proteins can be performed by mass spectrometry/liquid chromatography‑mass spectrometry (LC‑MS). The amino acid sequence of a protein can be detected by using tandem mass spectrometry. In this article, a review has been made on the sources, isolation, purification and characterization of natural proteins.
Keywords: Amino acid; natural proteins; SDS gel electrophoresis; salting out